CELLULAR CHANGES IN CARDIOMYOCYTES DUE TO ISCHEMIA AND NECROSIS - Ibragimova Ziyodaxon Jalolidinovna; G’anijonov Humoyunmirzo Ibroxim o’gli (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the biochemical study of the blood of patients with hypoxic myocardial ischemia, an increase in the MV fraction of troponins of creatine phosphokinase (CPK-MB) and lactate dehydrogenase (LDH) is observed.